The Central Projection of Cephalic Mechanosensory Axons in the Haematophagous Bug Triatoma infestans - Insausti, T.C. (2000)
The projections of mechanosensory hairs located on the dorsal and lateral head of the adult haematophagous bug Triatoma infestans were analyzed by means of cobalt filling. Axons run into the anterior and posterior tegumentary nerve and project through the brain to the ventral nerve cord. The fibres are small in diameter and run as a fascicle. Some branches run into suboesophageal and prothoracic centres; others run as far as to the mesothoracic ganglion. These sensory projections resemble that of wind-sensitive head hairs of the locust. The functional role of this sensory system in this species is discussed.